Face Mask Detection System Using Deep Learning - et. al., Mrs.Supriya Kurlekar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the present scenario due to Covid-19, there are no efficient face mask detection applications which are now in high demand for transportation means, densely populated areas, residential districts, large-scale manufacturers and other enterprises to ensure safety. This system can therefore be used in real-time applications which require face-mask detection for safety purposes due to the outbreak of Covid-19. This project can be integrated with embedded systems for application in airports, railway stations, offices, schools, and public places to ensure that public safety guidelines are followed.